1996
DOI: 10.1097/00007890-199603270-00028
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Concentrations of Soluble Class I Hla With Hla Allotypes

Abstract: We correlated serum concentrations of soluble class I HLA antigens (S-HLA-I) with HLA allotypes in 82 unrelated Caucasian and 58 unrelated African-American putatively normal subjects, as well as in 31 individuals with stable, normally functioning liver transplants. Caucasian and African-American subjects with HLA-A23 or HLA-A24 were high secretors of S-HLA-I. We also observed that some HLA-A allotypes associated with high serum concentrations of S-HLA-I were ethnicity specific. HLA-A33 was associated with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…In agreement with previous findings [20][21][22], controls and SLE patients with HLA allotype A9 had significantly higher serum concentration of sHLA-I compared to those with other allotypes (Figure 4). However, patients with allotype A2 did not show significantly lower levels of sHLA-I in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous findings [20][21][22], controls and SLE patients with HLA allotype A9 had significantly higher serum concentration of sHLA-I compared to those with other allotypes (Figure 4). However, patients with allotype A2 did not show significantly lower levels of sHLA-I in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The HLA-A23 and HLA-A24 (subgroups of the A9 allotype) are associated with high serum concentrations of sHLA-I, and HLA-A2 with low sHLA-I concentrations [20][21][22]. It is also known that the risk of developing SLE is increased in subjects carrying certain MHC haplotypes, in the case of HLA-A allotypes the HLA-A1 variant [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Here, neither HLA-G*01:04 nor HLA-A*23:01∼HLA-G*01:04∼UTR3 showed any significant difference in sHLA-G levels. Several explanations are possible, for example the high levels of sHLA class-I molecules reported in the serum of HLA-A*23 and HLA-A*24 individuals might have cross-reacted with the HLA-G antibody [62], [63], [64], [65]. Interestingly it has been suggested that the HLA-A*23:01∼HLA-G*01:04 haplotype may constitute a risk factor for allograft rejection in renal transplantation [66].…”
Section: Discussionmentioning
confidence: 99%
“…It has been documentedthat certain HLAphenotypes are associated with higher serum concentrations of sHLAs, and individuals with HLA-A23or HLA-A24have a higher value than those without these two antigens (19,20). However, our previous study of the association between HLAantigens and sarcoidosis in Japanese demonstrated the frequencies of these two antigens to be almost the same in both patients and control subjects (21).…”
Section: Discussionmentioning
confidence: 81%